Enveloped viruses distinct from HBV induce dissemination of hepatitis D virus in vivo - Perez-Vargas, Jimena; Amirache, Fouzia; Boson, Bertrand; Mialon, Chloé; Freitas, Natalia; Sureau, Camille; Fusil, Floriane; Cosset, François-Loïc (Nature communications, 2019)
Hepatitis D virus (HDV) doesn’t encode envelope proteins for packaging of its ribonucleoprotein (RNP) and typically relies on the surface glycoproteins (GPs) from hepatitis B virus (HBV) for virion assembly, envelopment and cellular transmission. HDV RNA genome can efficiently replicate in different tissues and species, raising the possibility that it evolved, and/or is still able to transmit, independently of HBV. Here we show that alternative, HBV-unrelated viruses can act as helper viruses for HDV. In vitro, envelope GPs from several virus genera, including vesiculovirus, flavivirus and hepacivirus, can package HDV RNPs, allowing efficient egress of HDV particles in the extracellular milieu of co-infected cells and subsequent entry into cells expressing the relevant receptors. Furthermore, HCV can propagate HDV infection in the liver of co-infected humanized mice for several months. Further work is necessary to evaluate whether HDV is currently transmitted by HBV-unrelated viruses in humans. Hepatitis D virus (HDV) relies on a helper virus to package and transmit its ribonucleoprotein (RNP). Here, Perez-Vargas et al. show that HDV can use envelope proteins from HBV-unrelated viruses, including HCV and flaviviruses, to propagate in vitro and in humanized mice.